DEVELOPMENT OF STEM-BASED SCIENCE LEARNING MODULE ON LOCAL WISDOM OF MANGO CULTIVATION IN PROBOLINGGO ON MODERN BIOTECHNOLOGY TOPIC - Istianah Istianah; Mochammad Iqbal (Program Studi Pendidikan IPA FKIP Universitas Jember, 2022)
This study aims to produce an integrated STEM science learning module with local wisdom